Hush the rush: Short-selling bans in times of stress - Armin Aminian (Bamberg University, Bamberg Economic Research Group (BERG), 2025)
Short-selling restrictions are often enacted during financial turmoil to promote market stability, though most research highlights their negative impact on market quality. This study examines the stability and effectiveness of these restrictions in preventing market crashes in an agent-based financial market model, where the fundamental value is controlled. The model features heterogeneous traders switching between momentum-based and valuation-based strategies and a leveraged long-term investor. This design incorporates herding, extrapolate behavior, and deleveraging - key drivers behind market crashes. The findings corroborate previous research, indicating that short-selling bans hinder downward price discovery and lead to inflated prices. By distinguishing the effects above and below the fundamental value, the study shows that while positive price distortion increases, negative price distortion and crash severity decrease. This suggests that short-selling restrictions enhance price efficiency and stability below the fundamental value. Furthermore, the mitigation of crash dynamics along with corresponding behavioral drivers and network effects indicates that temporary short-selling bans contribute to systemic stability.
urn:nbn:de:bvb:473-irb-110695x
Keywords: G19; G40; 330; Short-selling restrictions; Financial stability; Heterogeneous agents; Leverage; Herd behavior